Anisotropic surface roughness and shear behaviors of rough-walled plaster joints under constant normal load and constant normal stiffness conditions - Richeng Liu; Sha Lou; Xiaojing Li; Guansheng Han; Yujing Jiang (Journal of Rock Mechanics and Geotechnical Engineering, 2020)
In this context, we experimentally studied the anisotropic mechanical behaviors of rough-walled plaster joints using a servo-controlled direct shear apparatus under both constant normal load (CNL) and constant normal stiffness (CNS) conditions. The shear-induced variations in the normal displacement, shear stress, normal stress and sheared-off asperity mass are analyzed and correlated with the inclination angle of the critical waviness of joint surfaces. The results show that CNS condition gives rise to a smaller normal displacement due to the larger normal stress during shearing, compared with CNL condition. Under CNL conditions, there is one peak shear stress during shearing, whereas there are no peak shear stress for some cases and two peaks for other cases under CNS conditions depending on the geometry of joint surfaces. The inclination angle of the critical waviness has been verified to be capable of describing the joint surface roughness and anisotropy. The joint surface is more significantly damaged under CNS conditions than that under CNL conditions. With increment of the inclination angle of the critical waviness, both the normal displacement and sheared-off asperity mass increase, following power law functions; yet the coefficient of determination under CNL conditions is larger than that under CNS conditions. This is because the CNS condition significantly decreases the inclination angle of the critical waviness during shearing due to the larger degree of asperity degradation. Keywords: Joint, Constant normal load (CNL), Constant normal stiffness (CNS), Shear anisotropy, Surface roughness